2008
DOI: 10.3844/ajbbsp.2008.408.415
|View full text |Cite
|
Sign up to set email alerts
|

Investigations in the molecular events of Transitional Cell Carcinoma of the Bladder

Abstract: Problem Statement: Transitional Cell Carcinoma (TCC) of the bladder is a significant health problem worldwide. The molecular mechanisms of tumor development and progression are complicated but likely involve the interaction of tumor suppressor genes, oncogenes, cell cycle regulatory proteins and other factors. Hence this study tries to explore the role of p53, bcl-2, c-myc and Ki-67 in TCC of the bladder in correlation with different clinicopathological criteria which are tumor grade, muscle invasion by the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…These differences could be explained the selection criteria and sample size. In this study, 14 (43.8%) out of 32 patients were with low grade TCC while 18(56.2%) were with high grade TCC which disagree with other study done by Kadhim et al [37] there sample where include in the region of Middle East (Jordan, Syria and Iraq) who found that 66% of cases where with high grade tumor versus 33% where of low grade tumor. Probably, different environmental and ethnic factors operate in these three countries.…”
Section: Discussioncontrasting
confidence: 94%
“…These differences could be explained the selection criteria and sample size. In this study, 14 (43.8%) out of 32 patients were with low grade TCC while 18(56.2%) were with high grade TCC which disagree with other study done by Kadhim et al [37] there sample where include in the region of Middle East (Jordan, Syria and Iraq) who found that 66% of cases where with high grade tumor versus 33% where of low grade tumor. Probably, different environmental and ethnic factors operate in these three countries.…”
Section: Discussioncontrasting
confidence: 94%
“…Another famous antiapoptotic protein, Bcl-2, prevents Bax/Bak interaction, subsequent cytochrome c release, and caspase activation [ 39 ]. Aberrant Bcl-2 staining expressed significant association with tumor grade and tumor invasiveness in the TCC of the bladder [ 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This innate ability of V. amygdalina leaf extract to recognize the cancer patient's normal body cells as "self" cells and to recognize the malignant cancerous cells as "non self" cells that must be destroyed/inhibited from proliferating is a demonstration of the immune defence properties of Vernonia amygdalina leaf extract. The cancer tissue cytotoxicity/inhibition effects of Vernonia amygdalina leaf extract and powder obtained in these two therapeutic cases are concluded to be a demonstration of the free radical immune defence/antibody properties (Barrett and Blanc, 2009;Kadhim et al, 2008) of Vernonia amygdalina leaf extract and powder.…”
Section: Resultsmentioning
confidence: 99%